Quantifying the comprehensive benefit of the bike-sharing system under cycling behavior differences. (15th December 2022) - Zhi, Danyue; Sun, Huijun; Lv, Ying; Xu, Guangtong
Abstract: Bike-sharing (BS) as one of the sustainable travel modes, has become increasingly popular in cities around the world. However, the comprehensive benefit (CB) derived from multiple impacts in terms of environmental, time, convenience, and payment perspectives have not been well investigated. The study proposes an Environment-Time-Convenience-Payment (ETCP) model to quantitatively evaluate the CB of different clusters of BS users. More than 340, 000 BS users in Beijing are clustered into 6 groups through a two-stage clustering algorithm, which are low-frequency travel users, subway-dependent users, less subway-dependent users, long-distance travel users, work purpose users, and BS preferred users. On this basis, 8 alternative scenarios of BS are suggested to address the mode substitution uncertainty. The study monetizes the CO2 emission and the travel-related time, so that various benefits can be quantified and estimated uniformly. The results show that long-distance travel users can bring positive CBs under all scenarios, with an average CB of 1.01 to 6.47 RMB per day for each user. Although BS usage could increase CO2 emissions under most scenarios, it would correspond to travel time or/and hassle time savings at the same time. This study also investigates the beneficial differences between dock-based and dock-less BSs existing in different cities. The dock-based system in Chicago could provide the best environmental benefit, while the dock-less one in Beijing is relatively lower due to its flexibility with more short-distance trips. Highlights: The ETCP method can estimate the comprehensive benefit of the bike-sharing system. It tackles the mode substitution uncertainty under cycling behavior differences. It monetizes CO2 emissions and compares different benefits. It analyzes the tradeoff of various impacts and promotes bike-sharing development.